The role of North Atlantic–European weather regimes in the surface impact of sudden stratospheric warming events - Domeisen, Daniela; id_orcid:0 000-0002-1463-929X; Grams, Christian M.; Papritz, Lukas; id_orcid:0 000-0002-2047-9544 (Copernicus, 2020)
Sudden stratospheric warming (SSW) events can significantly impact tropospheric weather for a period of several weeks, in particular in the North Atlantic–European (NAE) region. While the stratospheric forcing often projects onto the North Atlantic Oscillation (NAO), the tropospheric response to SSW events, if any, is highly variable, and what determines the existence, location, timing, and strength of the downward impact remains an open question. We here explore how the variable tropospheric response to SSW events in the NAE region can be characterized in terms of a refined set of seven weather regimes and if the tropospheric flow in the North Atlantic region around the onset of SSW events is an indicator of the subsequent downward impact. The weather regime analysis reveals the Greenland blocking (GL) and Atlantic trough (AT) regimes as the most frequent large-scale patterns in the weeks following an SSW. While the GL regime is dominated by high pressure over Greenland, AT is dominated by a southeastward-shifted storm track in the North Atlantic. The flow evolution associated with GL and the associated cold conditions over Europe in the weeks following an SSW occur most frequently if a blocking situation over western Europe and the North Sea (European blocking) prevailed around the SSW onset. In contrast, an AT regime associated with mild conditions over Europe is more likely following the SSW event if GL occurs already around SSW onset. For the remaining tropospheric flow regimes during SSW onset we cannot identify a dominant flow evolution. Although it remains unclear what causes these relationships, the results suggest that specific tropospheric states in the days around the onset of the SSW are an indicator of the subsequent tropospheric flow evolution in the aftermath of an SSW, which could provide crucial guidance for subseasonal prediction. ISSN:2698-4016 ISSN:2698-4008